Tissue-specific silencing of integrated transgenes achieved through endogenous RNA interference in Caenorhabditis elegans - Siyu Chen; Weihong Liu; Lei Xiong; Zhiju Tao; Di Zhao (RNA Biology)
Transgene silencing is a common phenomenon observed in Caenorhabditis elegans, particularly in the germline, but the precise mechanisms underlying this process remain elusive. Through an analysis of the transcription factors profile of C. elegans, we discovered that the expression of several transgenic reporter lines exhibited tissue-specific silencing, specifically in the intestine of C. elegans. Notably, this silencing could be reversed in mutants defective in endogenous RNA interference (RNAi). Further investigation using knock-in strains revealed that these intestine-silent genes were indeed expressed in vivo, indicating that the organism itself regulates the intestine-specific silencing. This tissue-specific silencing appears to be mediated through the endo-RNAi pathway, with the main factors of this pathway, mut-2 and mut-16, are significantly enriched in the intestine. Additionally, histone modification factors, such as met-2, are involved in this silencing mechanism. Given the crucial role of the intestine in reproduction alongside the germline, the transgene silencing observed in the intestine reflects the self-protective mechanisms employed by the organisms. In summary, our study proposed that compared to other tissues, the transgenic silencing of intestine is specifically regulated by the endo-RNAi pathway.